Spatial Characteristics of Wideband Channels Using Leaky Coaxial Cables in Tunnel Scenario - Asad Saleem; Min Wang; Guoxin Zheng; Xiaoyu Yin (International Journal of Antennas and Propagation)
This paper presents the spatial domain and propagation characteristics of different wideband channels using leaky coaxial cables (LCXs) for underground environment at 1.8GHz corresponding to the Long Term Evolution for Metro (LTE-M) standards. Angular dispersion of the signal significantly affects the channel capacity, and it can be exactly predicted in both the near and far fields for underground environments by means of a multimode waveguide. A ray tracing phenomenon was exploited to visualize the wave propagation for different transmitter and receiver antenna distances by using the time domain approach for both the horizontally and vertically polarized LCXs. In order to achieve this goal, we characterized the power azimuth spectrum (PAS) and power angle profile (PAP) for different tunnel dimensions and found that the PAS can be demonstrated by a zero-mean Gaussian distribution whose angular spread (AS) is dependent on the transmitter-receiver distances and the tunnel dimensions. The results demonstrate that the horizontally polarized LCX has higher angular spread values than the vertically polarized one, and the correlation coefficient follows the decreasing function with the increment of angular spread.